Pelaksanaan Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor P 83 Tahun 2016 tentang Perhutanan Sosial sebagai upaya Revitalisasi Taman Nasional Tesso Nilo - Romes Irawan Putra (Jurnal Hukum Respublica, 2020)
The problem that will be discussed in this research is how to implement the Minister of Environment and Forestry Regulation Number P 83 of 2016 concerning Social Forestry as an Effort to Revitalize the Tesso Nilo National Park. This type of research is sociological, so the source of data used is primary data from interviews, secondary data from libraries and tertiary data from dictionaries, media, and encyclopedias. Data collection techniques are done by observation, interviews, and literature review. The implementation of Social Forestry as an effort to revitalize TNTN in the former PT Siak Raya Timber HPH area and the former PT Hutani Sola Lestari HPH area has been carried out to the affected communities, conducting an inventory and assistance in 4 (four) villages of Logas Tanah Tanah District, Kuantan Singingi Regency, namely Situgal Village, Hulu Tesso, Sidodadi, Giri Sako and Kesuma Village, Pangkalan Kuras District, Pelalawan Regency. However, not all villages have proposed Social Forestry, only Giri Sako Village has submitted a proposed Huta Village covering an area of ​​7,613.12 ha and Kesuma Village has an opportunity of 15,000 ha and is still in the preparation stage for submitting a Village Forest proposal. Various efforts were made to implement Social Forestry in TNTN, such as: a) Approach by the TNTN Balai both preventive and repressive to the community in and around TNTN, b) Integrated Operation of Handling and Safeguarding the Tesso Nilo Forest Area by uprooting oil palm covering an area of ​​175-180 ha, d) The Ministry of Environment and Forestry carries out a series of activities to revitalize the Tesso Nilo National Park involving the central and regional governments by identifying, inventorying, verifying areas and problems occurring on the ground.